Multicultural-Based Learning of Islamic Religious Education for the Development of Students' Social Attitudes - Sechandini, Radhia Ainun; Ratna, Rizky Dwi; Zakariyah, Zakariyah; Na’imah, Farida Ulvi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This article aims to describe and analyze the implementation of multiculturalism-based Islamic religious education for the development of students' social attitudes in the school environment. This research uses a qualitative type with a case study method approach. The use of three data collection techniques, namely, observation, interviews, and documentation. Data analysis was carried out in four stages according to Huberman and Miles, namely, data collection, data reduction, data presentation, and drawing conclusions. As well as the validity of the data used triangulation. The findings of this article show: First, multicultural-based Islamic Religious Education is well implemented in accordance with the Free Learning Curriculum which contains Pancasila Student Profiles in it according to the vision and mission of the Ministry of Education and Culture. The teacher uses 3 learning components according to Degeng, taking into account the conditions, methods, and learning outcomes then internalizing by planning, implementing, and evaluating learning. Second, through instilling and understanding Islamic values in learning activities inside the classroom and outside the classroom, multicultural-based Islamic Religious Education in the development of social attitudes has shown a positive outlook, such as by responding and responding through activeness, harmony, and togetherness.